2018
DOI: 10.1371/journal.pone.0193456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical stretching on the morphology of extracellular polymers and the mRNA expression of collagens and small leucine-rich repeat proteoglycans in vaginal fibroblasts from women with pelvic organ prolapse

Abstract: To determine the effect of mechanical stretching load and the efficacy of postmenopausal estrogen therapy (ET) on pelvic organ prolapse (POP), vaginal fibroblasts isolated from postmenopausal women with or without POP were subjected to 0.1-Hz uniaxial cyclic mechanical stretching (CS) with 10% elongation and 10−8 M 17-β-estradiol (E2) treatment. We investigated the morphological characteristics of extracellular polymers using scanning electron microscopy (SEM) and monitored the mRNA expression of type I collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
(60 reference statements)
2
14
0
2
Order By: Relevance
“…Here, we show specifically that the production of α-SMA in control fibroblasts is triggered by changes in both the ECM content and the surface micro-stiffness; whereas in POP fibroblasts, surface micro-stiffness seems to be the main driver of production of α-SMA. This higher mechano-sensitivity to surface stiffness by POP fibroblasts has recently been observed by others [31].…”
Section: Discussionsupporting
confidence: 83%
“…Here, we show specifically that the production of α-SMA in control fibroblasts is triggered by changes in both the ECM content and the surface micro-stiffness; whereas in POP fibroblasts, surface micro-stiffness seems to be the main driver of production of α-SMA. This higher mechano-sensitivity to surface stiffness by POP fibroblasts has recently been observed by others [31].…”
Section: Discussionsupporting
confidence: 83%
“…If the connective tissue is altered, the behavior of the fascia and underlying muscle becomes compromised, being source of myofascial disorders in many cases [28]. These results are in line with other studies: a recent work demonstrated that vaginal fibroblasts isolated from postmenopausal women with pelvic organ prolapse show higher sensitivity and lower tolerance to mechanical stretching with respect to normal fibroblasts, with higher expression of collagen-I and a lower expression of collagen-III mRNA [29]. This work provides evidence supporting estrogen therapy to prevent and inhibit prolapse in postmenopausal women.…”
Section: Discussionsupporting
confidence: 83%
“…The degradation of col is predominantly mediated by MMPs, while col synthesis is regulated by TiMPs (30). Previous studies have demonstrated that the levels of col-i and col-iii are downregulated in PoP tissues (31,32). However, the molecular mechanism underlying downregulation of col in PoP remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%